2004
DOI: 10.1002/jez.a.20026
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopancreas gluconeogenesis during anoxia and post‐anoxia recovery in Chasmagnathus granulata crabs maintained on high‐protein or carbohydrate‐rich diets

Abstract: C. granulata is a semiterrestrial crab that lives in the mesolittoral and the supralittoral zones of estuaries and faces hypoxia and anoxia when exposed to atmospheric air. The carbohydrate or protein content of the diets administered to the crabs induced different metabolic adjustments during anoxia and post-anoxia recovery period. During the first hour in anoxia a marked increase in L-lactate concentration in hemolymph was induced, followed by a reduction in its levels accompanied by two peaks in hepatopancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…These values of glucose are similar to those obtained in the crab C. granulatus maintained in laboratory conditions on a high-protein diet (KUCHARSKI & DA SILVA, 1991a;OLIVEIRA et al, 2004), and contrast with the results observed in crabs and lobster maintained on a carbohydrate-rich diet, which showed increased levels of circulating glucose (VINAGRE & DA SILVA, 1992;RADFORD et al, 2005). We can therefore infer that the natural diet of P. brasiliensis is high in protein and low in carbohydrate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These values of glucose are similar to those obtained in the crab C. granulatus maintained in laboratory conditions on a high-protein diet (KUCHARSKI & DA SILVA, 1991a;OLIVEIRA et al, 2004), and contrast with the results observed in crabs and lobster maintained on a carbohydrate-rich diet, which showed increased levels of circulating glucose (VINAGRE & DA SILVA, 1992;RADFORD et al, 2005). We can therefore infer that the natural diet of P. brasiliensis is high in protein and low in carbohydrate.…”
Section: Discussionsupporting
confidence: 85%
“…The absence of a central glycogen deposit seems to be an adaptation of several classes of animals to changes in environmental factors (HOCHACHKA et al, 1970). The stored glycogen is utilized in adaptation to molting, hypoxia and/or anoxia, osmoregulation, growth, reproduction and during fasting periods (CHANG & O'CONNOR, 1983;KUCHARSKI & SILVA, 1991a, 1991bOLIVEIRA et al, 2001OLIVEIRA et al, , 2004.…”
mentioning
confidence: 99%
“…OLIVEIRA & DA SILVA (1997) demonstrated a high gluconeogenic capacity in the hepatopancreas of crabs, fed either protein-or carbohydrate-rich diets. These authors concluded that the gluconeogenic pathway is important for the survival of the estuarine crab (C. granulatus) during periods of wide environmental variations, such as salinity, food scarcity, and dissolved-oxygen levels (OLIVEIRA et al, 1997(OLIVEIRA et al, , 2001(OLIVEIRA et al, , 2004a. Hemolymphatic glucose is the result of the influx of intestinal glucose (VERRI et al, 2001), and from the balance between anabolic (gluconeogenic, glycogenesis and catabolic, glycogenolysis, glycolysis) processes (CHANG & O'CONNOR, 1983;OLIVEIRA & DA SILVA, 1997;HALL & VAN HAM, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a central glycogen deposit seems to be an adaptation of several classes of animals to changes in environmental factors (HOCHACHKA et al, 1970). The stored glycogen is utilized in adaptation to molting, hypoxia and/or anoxia, osmoregulation, growth, in different stages of reproduction and during fasting periods (CHANG & O'CONNOR, 1983;KUCHARSKI & SILVA, 1991a, b;OLIVEIRA et al, 2001OLIVEIRA et al, , 2004a.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, easy access, suitable size and high-stress tolerance made this species of crab a frequently used invertebrate model for experimental studies of metabolic physiology (e.g. Oliveira et al 2004;Schein et al 2005a;Marqueze et al 2006), pollution eVects (e.g. Abigail et al 2003;Medesani et al 2004a, b;Menone et al 2004), and of the neurological and molecular basis of behaviour, learning and memory (e.g.…”
Section: Introductionmentioning
confidence: 99%